Physical medicine and rehabilitation secrets (Hanley & Belfus, 2002)
A physiatry text in Q&A format linking data from the literature, textbooks, and research; it's intended as a resource for residents, students, interns, faculty, and clinicians in any specialty. The second edition revises the "bread, butter, and board" topics of physical medicine and rehabilitation, and includes new chapters on recent advances such as interventional physiatry and transplantation rehabilitation.